2008
DOI: 10.1292/jvms.70.1051
|View full text |Cite
|
Sign up to set email alerts
|

Branching Pattern of Aortic Arch in the Korean Water Deer

Abstract: ABSTRACT. This study examined the branching pattern of the aortic arch and its major branches in Korean water deer (Hydropotes inermis argyropus, Heude, 1884). Silicone casts were taken from the vessels of 23 carcasses (male 14, female 9) with body weights ranging from 1.3-16.0 kg through a retrograde injection into the abdominal aorta. The findings were compared with those from other domestic ruminants. Only the brachiocephalic trunk (Bct) branched from the aortic arch in all carcasses. In 19 of the 23 cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 6 publications
0
31
1
Order By: Relevance
“…The male genital organs [31], the rumen structure [21] and the branching pattern of the aortic arch [4] have been anatomically studied in the Korean water deer. In the genus Muntjac, the parotid and mandibular glands [1], lingual papillae [2,37], endocrine cells in the gastrointestinal tract [3], Harderian and nictitans glands [28] and facial scent gland [9] have been anatomically and histologically observed.…”
mentioning
confidence: 99%
“…The male genital organs [31], the rumen structure [21] and the branching pattern of the aortic arch [4] have been anatomically studied in the Korean water deer. In the genus Muntjac, the parotid and mandibular glands [1], lingual papillae [2,37], endocrine cells in the gastrointestinal tract [3], Harderian and nictitans glands [28] and facial scent gland [9] have been anatomically and histologically observed.…”
mentioning
confidence: 99%
“…For this purpose, rodents (Sinzinger and Hohenecker 1972;Atalar et al 2003;Aydin 2011), ruminants (Lee and Lee, 1984;Ahn et al 2008), and carnivores (Rochat and Settles 1993;Ricardo et al 2001;Kim et al 2006) have been studied. In addition, pathologic variations of the aortic arch were also investigated in humans and animals (Yarim et al 1999;Yoo et al 2003;Yeri et al 2011), and these variations are reported to be significant occurrences alongside the normal anatomical situation.…”
mentioning
confidence: 99%
“…L cells that stably expressed stabilin-2 (Stab-2/L cells) were grown in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% heat-inactivated fetal bovine serum (FBS), as previously described (1). To generate L cells expressing Stab2⌬C, the cells were transfected with the pcDNA-Stab2⌬C vector and selected in G418 (400 g/ml).…”
Section: Reagents and Antibodiesmentioning
confidence: 99%